Zmiany w stosunku służbowym funkcjonariuszy państwowej służby cywilnej w II Rzeczypospolitej - Krzymkowski, Marek (Czasopismo Prawno-Historyczne, 2018)
Legal situation of the civil servants in the Second Polish Republic was regulated by the act of the 17th of February 1922 on the state civil service. Employment in the civil service was public in character. The changes in the employment of the state civil servants could take different forms. Among them were the following: transferring a civil servant to a different town and to a different position; transferring a civil servant to “a position which is subjected to different regulations” within the same department of the state administration; transferring to a different department of the state administration at the request of a civil servant; changing the employee’s status to inactive state; releasing civil servants to a legislative body and freeing them from professional duties for the duration of their mandate in the said body.